Representasi Status Sosial Dalam Cerpen “Juru Masak” Karya Damhuri Muhammad: Perspektif Stratifikasi Sosial Max Weber: Penelitian - Rizqy Munazila Eka Rosyadi; Anas Ahmadi; Moh. Ahsan Shohifur Rizal (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the representation of social stratification in the short story Juru Masak by Damhuri Muhammad using Max Weber’s perspective, which includes class, status, and power dimensions. This research employs a qualitative approach with a descriptive-analytical method. The data source is the text of the short story, while the data are in the form of narrative and dialogue units that reflect social stratification indicators. Data were collected through a reading and note-taking technique and analyzed using data reduction, data display, and conclusion drawing. The results show that: (1) social class is constructed through occupation and economic ownership, where economic capital determines an individual’s position in the social hierarchy; (2) social status operates through symbolic recognition and social honor, functioning as a mechanism of social closure that restricts social relations, particularly in marriage; and (3) social power is represented not only through economic domination but also through cultural authority based on collective recognition. The findings indicate that social stratification in the story is multidimensional and dynamic, revealing tensions between economic mobility and the persistence of symbolic status structures.